5x+30x-9=7(5x+3)

Simple and best practice solution for 5x+30x-9=7(5x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+30x-9=7(5x+3) equation:


Simplifying
5x + 30x + -9 = 7(5x + 3)

Reorder the terms:
-9 + 5x + 30x = 7(5x + 3)

Combine like terms: 5x + 30x = 35x
-9 + 35x = 7(5x + 3)

Reorder the terms:
-9 + 35x = 7(3 + 5x)
-9 + 35x = (3 * 7 + 5x * 7)
-9 + 35x = (21 + 35x)

Add '-35x' to each side of the equation.
-9 + 35x + -35x = 21 + 35x + -35x

Combine like terms: 35x + -35x = 0
-9 + 0 = 21 + 35x + -35x
-9 = 21 + 35x + -35x

Combine like terms: 35x + -35x = 0
-9 = 21 + 0
-9 = 21

Solving
-9 = 21

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -7x+4y=10 | | 0+6x=11 | | 5x+10=-7x+94 | | 6y*2y=12y^2 | | 7*2x+28=0 | | 2n^2+18n-44=0 | | 4x-(0.03x)=79.59 | | 4y=3x-7+128 | | 3x-2(4x-5)=3x-14 | | -7+14+8x=5+x+9 | | 5r^2+34r-7= | | 2(3t-6)=11t+7 | | -23.02(X-2.74)=63.72 | | 7x+6=7x-10 | | (2+9i)+(7+2i)(7-2i)= | | 7x+6=7x-7 | | 3x-8+3=55 | | 5-x=-7x+35 | | 6x+2-3x=4x+7-3 | | 3x^2-18x+26=0 | | 5/7-5/21= | | 2(x-3)+6x=x+8 | | 11+9(-3-9)=-32+11n | | 7r^2-10r-8= | | 248-U=67 | | 3x^2-18+26=0 | | 10x+3y+6z-5x+2z-7y= | | 2(x-3)+3(x+1)=7 | | 6(-5x-8)=228 | | 10x-10=22x+6x+18 | | h(0.8)=10.4 | | 40=4x-x+4 |

Equations solver categories